ERIC CLARKS' TRAUMA IN RODRIGO GARCIA'S PASSENGERS MOVIE (2008): A PSYCHOANALYTIC APPROACH - RADITYA, KARIM (2011)
The major problem of the research on Passangers movie is how trauma is described in character of Passangers movie. Meanwhile, this problem is limited to the minor character Eric Clark viewed by psychoanalytic approach. The objective of the study is to analyze movie based on the structural elements and the personality of the minor character based on psychoanalytic approach. The benefit of the study is to give additional information that can be used by the other literature researchers who are interested in analyzing this movie. The writer conducts the research by using qualitative method that uses the library research, while the data sources are literary data that are divided into two categories, primary and secondary data. The primary data are the movie subtitle Passengers itself and the secondary data include several references books of Psychoanalysis. The object of the research is the movie entitled Passengers directed by Rodrigo Garcia. The results of the study are as follows. Firstly, the structural elements of the movie present a unity. It appears in the beginning, the middle, and the end of the story. Secondly, the psychoanalytic analysis shows that trauma leads the effect of life such as the feeling of panic, fear, shock, and confusion.